Temperature dependence of backward tunnel diode oscillator circuit. (May 2020) - El-Basit, W. Abd; Awad, Z.I.M.; Kamh, S.A.; Soliman, F.A.S.
Abstract: In the present paper, a package of BD-4 germanium backward tunnel diodes, which widely used in modern electronic systems were chosen for studying its operation as an oscillator circuit under the influence of a wide range of temperatures ranging from 100 ​K up to 343 ​K. The electrical parameters of the devices based on their I – V characteristics were investigated, where it is clear that peak-to-valley current ratio, valley voltage, forward voltage, voltage span, voltage swing, and current span were decreased from 12.9, 0.35 ​V, 0.65 ​V, 0.31 ​V, 0.65 ​V, and 50.70 ​μA down to 3.2, 0.22 ​V, 0.35 ​V, 0.17 ​V, 0.30 ​V, and 31.30 ​μA, respectively. On the other hand, both peak voltage and negative differential resistance were shown to be almost temperature independent. Besides, a simple sinusoidal LC oscillator circuit that operates at 2.30 ​MHz was designed, implemented and tested, where its output signal voltage waveforms were plotted at different temperature levels within the investigated range. On the other hand, it was shown that the oscillation frequency, peak-to-peak voltage, output power spectrum, and phase-noise were temperatureindependent provided that the diode is adequately biased in its negative resistance region. Finally, the obtained results were shown to be in good agreement in the trend with that previously published.